Tuning the Spin State of Co Accelerates Hydrogen Evolution Reaction of Pt Nanoparticles - Qian Zheng; Wei An; Jianxin Pan; Fengshan Yu; Yizhang Du; Jian Cui; Weiyu Song; Shengming Xu; Chunxia Wang; Guoyong Huang; Yi‐Ming Yan (SusMat)
ABSTRACT The quest for dynamic and cost‐effective electrocatalysts to substitute carbon‐supported platinum (Pt) in alkaline hydrogen evolution reaction (HER) remains a pressing challenge. The incorporation of transition metal atoms through electron donation and spin regulation dominates the HER performance of Pt nanoparticles. Herein, we demonstrate that Co‐N coordination was utilized to regulate and stabilize the chemical microenvironment of Pt nanoparticles to fabricate hybrid electrocatalysts (Pt/CoNC). The resultant Pt/CoNC delivers ultralow overpotentials of 15.2 and 171.2 mV at current densities of 10 and 100 mA cm−2, surpassing commercial Pt/C. The poisoning tests, where η10 values of Pt/CoNC depict negative shifts of 161 and 13 mV by potassium thiocyanide (KSCN) and ethylenediaminetetraacetic acid disodium (EDTA), suggest the combined impact of Pt nanoparticles and Co‐N coordination on HER, with Pt nanoparticles playing a decisive role. The magnetic characterization and spin density diagrams reveal that Pt induces a higher spin state of Co2+, creating a wider spin‐related channel for electron donation to Pt. Moreover, Co‐N effectively modifies the electronic structure of Pt, thereby reducing the energy barriers for H2O dissociation (from 0.41 to −0.22 eV) and H2 generation (from −0.35 to 0.03 eV). This finding provides insights to fabricate advanced electrocatalysts through regulating spin state and modulating interfacial electron transfer.